2001
DOI: 10.1161/hc4901.100379
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inducible Nitric Oxide Synthase Depresses β-Adrenergic–Stimulated Calcium Release From the Sarcoplasmic Reticulum in Intact Ventricular Myocytes

Abstract: Background-␤-Adrenergic hyporesponsiveness in many cardiomyopathies is linked to expression of inducible nitric oxide synthase (iNOS) and increased production of NO. The purpose of this study was to examine whether iNOS expression alters the function of the sarcoplasmic reticulum (SR) Ca 2ϩ release channel (ryanodine receptor, RyR) during ␤-adrenergic stimulation. Methods and Results-Expression of iNOS was induced by lipopolysaccharide (LPS) injection (10 mg/kg) 6 hours before rat myocyte isolation. Confocal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 42 publications
3
44
0
4
Order By: Relevance
“…Several early studies reported that activation of NOS with increased NO production tends to decrease contractility via cGMP-dependent or cGMP- independent mechanisms (3,6,7,12,17,43). Moreover, as recently reviewed, analysis of the phenotypes of mice genetically deficient in one or more isoforms of NOS further supports the conclusion that NO signaling tends to attenuate contractility under basal conditions (28).…”
Section: Discussionmentioning
confidence: 87%
“…Several early studies reported that activation of NOS with increased NO production tends to decrease contractility via cGMP-dependent or cGMP- independent mechanisms (3,6,7,12,17,43). Moreover, as recently reviewed, analysis of the phenotypes of mice genetically deficient in one or more isoforms of NOS further supports the conclusion that NO signaling tends to attenuate contractility under basal conditions (28).…”
Section: Discussionmentioning
confidence: 87%
“…However, a coherent hypothesis detailing the role of specific NOS isoforms and the locus of action of NO in heart failure has not yet emerged. Some studies indicate that cytokine-induced NOS2 and NO production cause suppression of myocyte Ca 2ϩ transients (35)(36)(37)(38). However, it has more recently been shown that constitutive NOS isoforms contribute to the heart failure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of effect of low SIN-1 in PLB −/− myocytes may indicate that these positive effects are mediated via PLB-dependent mechanisms. However, the effects of low SIN-1 on other excitation-contraction coupling proteins cannot be completely ruled out, as peroxynitrite has been shown to have effects on other excitation-contraction coupling proteins [35][36][37][38][39]. Further, SIN-1 has a complex chemistry that could potentially lead to the formation of other reactive nitrogen species.…”
Section: Sin-1 and Plb −/− Myocyte Functionmentioning
confidence: 99%
“…NOS1 is considered a physiological regulator of cardiac function and is also thought to increase myocardial contractility [41]. Conversely, high SIN-1 may be mimicking the peroxynitrite production of NOS2, which is considered to be a pathophysiological regulator of cardiac function by reducing β-adrenergic responsiveness [3,36]. During many pathophysiological conditions of the myocardium, nitric oxide production is increased with NOS2 expression [3,42] and superoxide production is increased through NADPH oxidase and/or xanthine oxidoreductase [8,9], leading to supraphysiological peroxynitrite production and cardiac dysfunction.…”
Section: Sin-1 and Plb −/− Myocyte Functionmentioning
confidence: 99%